Preliminary Results of Assessing the Mixing of Wave Transport Flux Residualin the Upper Ocean with ROMS - Shi, Yongfang; Wu, Kejian; Yang, Yongzeng (Journal of Ocean University of China, 2016)
The effects of the mixing of wave transport flux residual （Bvl） on the upper ocean is studied through carrying out the control run （CR） and a series of sensitive runs （SR） with ROMS model. In this study, the Important role of Bvl is revealed by com- paring the ocean temperature, statistical analysis of errors and evaluating the mixed layer depth. It is shown that the overestimated SST is improved effectively when the wave-induced mixing is incorporated to the vertical mixing scheme. As can be seen from the vertical structure of temperature 28℃ isotherm changes from 20min CR to 35m in SR3, which is more close to the observation. Statistic analysis shows that the root-mean-square errors of the temperature in 10m are reduced and the correlation between model results and observation data are increased after considering the effect of Bvl. The numerical results of the ocean temperature show improvement in summer and in tropical zones in winter, especially in the strong current regions in summer. In August the mixed layer depth （MLD） which is defined as the depth that the temperature has changed 0.5℃ from the reference depth of 10m is further ana- lyzed. The simulation results have a close relationship with undetermined coefficient of Bvl, sensitivity studies show that a coeffi- cient about 0.1 is reasonable value in the model